2022
DOI: 10.1371/journal.pone.0264339
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of artemether-lumefantrine, artesunate-amodiaquine and dihydroartemisinin-piperaquine in the treatment of uncomplicated Plasmodium falciparum malaria in Sub-Saharan Africa: A systematic review and meta-analysis

Abstract: Background Sub-Saharan Africa has the highest burden of malaria in the world. Artemisinin-based combination therapies (ACTs) have been the cornerstone in the efforts to reduce the global burden of malaria. In the effort to facilitate early detection of resistance for artemisinin derivatives and partner drugs, WHO recommends monitoring of ACT’s efficacy in the malaria endemic countries. The present systematic meta-analysis study summarises the evidence of therapeutic efficacy of the commonly used artemisinin-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…PCR-corrected cure rates for all three sites on day 42 were over 90% (failure rates below WHO's threshold of 10% for partner drug resistance) (WHO, 2020), and therefore supports the inclusion of DHAP in the treatment policy for Ghana (MOH, 2020). High efficacy of DHAP has also been reported in other sub-Saharan African countries (Marwa et al, 2022) including Nigeria (Ebenebe et al, 2018), Sierra Leone (Smith et al, 2018), Mali (Dama et al, 2018), Guinea-Bissau (Ursing et al, 2016), Kenya (Westercamp et al, 2022), Tanzania (Mandara et al, 2019), Uganda (Ebong et al, 2021), Somalia (Warsame et al, 2019), Rwanda (Uwimana et al, 2019), and Angola (Davlantes et al, 2018). This notwithstanding PCRcorrected cure rate for WMH was significantly lower than HMH and EWP suggesting possible lower parasite susceptibility to piperaquine in WMH.…”
Section: Discussionmentioning
confidence: 75%
“…PCR-corrected cure rates for all three sites on day 42 were over 90% (failure rates below WHO's threshold of 10% for partner drug resistance) (WHO, 2020), and therefore supports the inclusion of DHAP in the treatment policy for Ghana (MOH, 2020). High efficacy of DHAP has also been reported in other sub-Saharan African countries (Marwa et al, 2022) including Nigeria (Ebenebe et al, 2018), Sierra Leone (Smith et al, 2018), Mali (Dama et al, 2018), Guinea-Bissau (Ursing et al, 2016), Kenya (Westercamp et al, 2022), Tanzania (Mandara et al, 2019), Uganda (Ebong et al, 2021), Somalia (Warsame et al, 2019), Rwanda (Uwimana et al, 2019), and Angola (Davlantes et al, 2018). This notwithstanding PCRcorrected cure rate for WMH was significantly lower than HMH and EWP suggesting possible lower parasite susceptibility to piperaquine in WMH.…”
Section: Discussionmentioning
confidence: 75%
“…[17][18][19][20][21][22] Artemesinin-based Combination Therapies (ACTs) are the most commonly used antimalarials in our study, which is consistent with their demonstrated efficacy for uncomplicated malaria in African settings in recent systematic reviews and meta-analyses. 23,24 Nonetheless, indiscriminate use of antimalarial drugs (ACTs) for self-diagnosed malaria will eventually lead to increased drug resistance, treatment failure, and complications. 25,26 Before treating children with malaria-like illnesses, appropriate rapid diagnostic testing should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Several alternative ACT regimens are also available. A recent systematic review and meta-analysis on the efficacy of ACTs used in Sub Saharan Africa from 2010 to 2020 reports an overall high success rate in the treatment of malaria using artesunate-amodiaquine, artemetherlumefantrine, and dihydroartemisinin-piperaquine in this region (Marwa et al, 2022). With the emergence of partial artemisininresistant P. falciparum in east Africa (Uwimana et al, 2020;Balikagala et al, 2021;Uwimana et al, 2021), regular surveillance of ACTs efficacy is critical and the availability of several ACTs in the region would be beneficial if properly used.…”
Section: The Alternate Use Of Different Antimalarial Regimensmentioning
confidence: 99%